Transmission of Sharia Monetary Policy in Improving Sharia Banking Performance (Literature Study) - Ikhsan Abdullah; Arnida Wahyuni Lubis; Rifki Ismail; Andri Soemitra (International Journal Of Economics Social And Technology, 2022)
Indonesia's economic condition is currently experiencing a downturn, even though its current growth has increased by 5 percent from before. This will be the impact of Covid 19 that hit the country. This impact has had an impact on the decline of banking in the country, especially Islamic banking since 2020. When compared to the profits obtained since 2019. This study aims to see the performance of Islamic banking when viewed from the current monetary policy. This study uses a qualitative method. Documentation technique for analyzing documents related to Islamic Banking performance. The data used in the analysis includes Islamic Banking Accounting books, research articles, and so on. Based on the results of research conducted that the performance of Islamic banking in the country can survive and experience a very satisfying increase, it can be seen that the increase is happening every year. In semester I/2021, the profit earned was IDR 1.48 trillion, an increase of 34.29%. In 2022 the profit earned is IDR 3.21 trillion, an increase of 42%. From the results of these observations, the current monetary policy carried out by BSI can improve the financial performance of Islamic banking, even though our economic growth is currently experiencing an economic crisis.